Pengaruh Model Probing Prompting terhadap Hasil Belajar Matematika Siswa Kelas VII SMP Islam Darusslam Kabupaten Gowa - Hastuti Agussalim; Arwin Wahyu Saputra; Muhammad Zakkir; Siti Maulida Hasanah; Nur Aisyah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study is a quasi-experimental study that aims to determine the effect of the Probing-Prompting model on the mathematics learning outcomes of seventh-grade students of SMP Islam Darussalam. The sample in this study consisted of class VII-A which was used as an experimental class, which was taught using the Probing-Prompting model, and class VII-B which was used as a control class, which was taught using the lecture method. Based on the results of descriptive statistical analysis, it was found that the group taught with the Probing-Prompting model had learning outcomes categorized as moderate with an average value of 60.41, while the group taught with the lecture method had learning outcomes categorized as low with an average value of 42.94. The results of the inferential analysis showed a t_count value of 2.388, while the t_table was 1.69. This indicates that the Probing-Prompting model has a significant influence on improving students' mathematics learning outcomes, where students taught with the Probing-Prompting model showed higher learning outcomes compared to students taught with the lecture method.